The impacts of community-based water development projects on rural poverty among small-holder farmers: Evidence from the Ewaso Ng'iro North Catchment Area, Kenya - Simon Nganga Mwaura; Isaac Maina Kariuki; Simon Kiprop; Augustus Sammy Muluvi; Gideon A. Obare; Boniface Kiteme (Cogent Economics & Finance, 2021)
The main challenge with respect to water in the rural setting, lies in access, control and management. Collective action has been taken up following the International Water Management (IWM) principles and institutionalized in the Kenyan legal framework through water resource users' associations (WRUAs). We carried out this study to assess whether this collective action has any impact on household poverty using objective poverty measures (consumption and income), a subjective poverty measure and a water poverty measure. We used 2019 household survey data of 652 randomly selected rural households from the Upper Ewaso Ng'iro North Catchment Area. We employed the full information maximum likelihood endogenous probit regression model to obtain the impact of WRUA membership on household poverty status. We find that collective water management can have welfare improving impacts for rural households, especially where there low public investments in water provision, management and access. We recommend that WRUAs be empowered through financial, legal and capacity building interventions to enhance their community impacts.
Keywords: 330; collective action; Objective poverty; rural poverty; subjective poverty; Upper Ewaso Ng'iro North Catchment; water poverty